Reforming Higher Education in Poland: Juridification and Practices of Simulation - Ostrowicka, Helena; Rzyska, Aleksandra (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
This article concerns juridification in Polish higher education, analyzed in the context of the reforms of the science and education sector from the 1990s until the present. Using the Polish example, we present juridification as a process which generates and legitimizes practices of simulation. This conception allows us to explain the development of legal discourse, along with its consequences in discursive and non-discursive practices. The main research question was how juridification manifests itself in the reforms of science and higher education in Poland after the political transformation of 1989. We included two types of sources: 1) secondary sources (previous research on the transformation of the higher education system in Poland) and 2) primary sources – key legal acts regulating the sector, with comments and materials provided by the Ministry. The development of mechanisms of juridification after 2011 strengthened the state’s position in managing science and higher education in Poland and consolidated the discourse of competition and rivalry in the name of scientific and didactic excellence. We do notice, however, that over the last few years the process of juridification has produced simulated activities within the university. The intense public debate about the role of the university stimulated academics to rethink their own practices and their own “self ” as researchers and academics. The actions that we interpret in terms of practices of simulation on the one hand reveal the conflict between the new ‘regime of truth’ and the traditional discourse, and on the other hand demonstrate the productive power relations in which we all as academics participate.